STAY NATURAL, STAY SAFE: GERAKAN CERDAS MENINGKATKAN KESADARAN MASYARAKAT KELURAHAN ANAWAI TERHADAP PENGGUNAAN OBAT TRADISIONAL YANG TEPAT DAN AMAN MELALUI EDUKASI BERBASIS LITERASI KESEHATAN - Pascayantri, Asniar; Hasnawati, Hasnawati; Irnawati, Irnawati; Munasari, Dian; Susanto, Agus Silfia; Nasrudin, Nasrudin; Sari, Indah Nurcahaya; Karimu, Laila Qodriyah; Sari, Mayang; Sudia, Nurfadillah; Anugrah, Padil; Ramadhani, Afifah Nur; Lisar, Angelina; Y, Muhammad Ilyas; Mubarak, Mubarak; Priliyani, Chetrin; Jabbar, Asriullah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The widespread use of traditional medicine in Indonesian communities is often not accompanied by adequate awareness of safety, legality, and rational use. This community service program, entitled “Stay Natural, Stay Safe”, aimed to enhance public awareness of proper and safe traditional medicine use through health literacy–based education in Anawai Village, Kendari City. The intervention employed a door-to-door pharmaceutical communication approach supported by printed educational leaflets as communication, information, and education (CIE) media. Activities were conducted through observation, educational counseling, practical demonstrations, and evaluation. The evaluation results showed a high level of community understanding, with a mean score of 4.49 and an achievement rate of 89.73%, categorized as very good. These findings indicate that health literacy–based education supported by leaflets effectively improves community awareness, confidence, and rational behavior in traditional medicine use and can serve as a sustainable community-based health promotion strategy.